2012
DOI: 10.1111/j.1475-6773.2012.01458.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Impact of the Affordable Care Act on Health Insurance Coverage of Young Adults

Abstract: Research Objective. To evaluate one of the first implemented provisions of the Patient Protection and Affordable Care Act (ACA), which permits young adults up to age 26 to enroll as dependents on a parent's private health plan. Nearly one-in-three young adults lacked coverage before the ACA. Study Design, Methods, and Data. Data from the Current Population Survey 2005 -2011 are used to estimate linear probability models within a difference-in-differences framework to estimate how the ACA affected coverage of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
154
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(163 citation statements)
references
References 10 publications
(18 reference statements)
8
154
1
Order By: Relevance
“…This finding is similar to associations found in studies of all adults aged ≥ years 18 in NHANES. 5,20 The Affordable Care Act, which allows individuals under age 26 to be covered as dependents under their parents' insurance 21 and requires preventive services be provided without any co-payment, holds promise for improving rates of screening, diagnosis, and treatment of CVD risk factors in young adults. However, additional efforts to keep youth connected to the health care system as they leave their pediatric medical home and transition to adulthood will likely be required as well.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is similar to associations found in studies of all adults aged ≥ years 18 in NHANES. 5,20 The Affordable Care Act, which allows individuals under age 26 to be covered as dependents under their parents' insurance 21 and requires preventive services be provided without any co-payment, holds promise for improving rates of screening, diagnosis, and treatment of CVD risk factors in young adults. However, additional efforts to keep youth connected to the health care system as they leave their pediatric medical home and transition to adulthood will likely be required as well.…”
Section: Discussionmentioning
confidence: 99%
“…We also find a 5.5 percent increase in mental-illness-related visits. Corresponding to these changes in service utilization, we 4 find that the fraction of hospitalized young adults without insurance decreased by 10.8 percent compared to other adults who did not benefit from the expansion. The implied estimate of the impact of this health insurance coverage on the probability of an inpatient visit is 85.4 percent.…”
Section: Introductionmentioning
confidence: 79%
“…Since access to parental ESI is associated with higher-income households, we explore the impact of the mandate by median zip code income quartiles of young adults on the assumption that even if young adult children of higher-income households no longer live in the same household as their parents, they are more likely to live in higher-income zip codes than other young adults. 4 We thus expect a larger impact of the mandate on young adults who reside in the higher median income quartiles.…”
Section: Heterogeneous Effect Of the Mandatementioning
confidence: 94%
“…As noted previously, there are alternative factors that could explain the increase in students receiving treatment. The passage of the Affordable Care Act (ACA) in 2010 has led to an increase in the number of young adults with health insurance, especially because they are allowed to remain covered by their parents' insurance through the age of 26 (Cantor et al, 2012;Sommers et al, 2013). Studies have shown that increasing insurance coverage leads to a corresponding increase in the receipt of health care, especially mental health care (Sommers et al, 2013).…”
Section: Context Assumptions and Limitationsmentioning
confidence: 99%
“…We note, however, that even prior to the ACA, it was common for many colleges to require that students have health insurance or to provide it to them and, given the timing of our sample waves, it is unlikely that expanding coverage due to the ACA accounts for all the change we observed. While the open enrollment period for the ACA began in 2013, most of the enrollment impact on young adults occurred shortly after the implementation of PEI programs in 2010 and 2011-as students were allowed to remain on their parents' health insurance plans through age 26-and prior to 2013 (Cantor et al, 2012;Sommers et al, 2013), when our first wave of data was collected.…”
Section: Context Assumptions and Limitationsmentioning
confidence: 99%